2004
DOI: 10.1124/jpet.104.070755
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Ascorbate and Light-Exposed Riboflavin Induces Lung Remodeling

Abstract: Light-exposed parenteral multivitamins induce in lungs peroxidelike oxidant responses as well as the initiation of fibrosis. We hypothesized that peroxides generated in light-exposed total parenteral nutrition (TPN) affect lung remodeling. The objective was to assess the specific roles of peroxides, multivitamin preparation (MVP), and light exposure on lung remodeling during TPN. Threeday-old guinea pigs fitted with an indwelling catheter were assigned to the following intravenous regimens: TPN or MVP Ϯ photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 38 publications
2
42
0
3
Order By: Relevance
“…Despite this negative effect of H 2 O 2 on caspase-3, the activation remained sufficient to induce a decrease in the alveolar number. The effect of ascorbylperoxide on alveolarization index was similar to the values previously reported in studies investigating the effect of parenteral nutrition [14,15]. …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Despite this negative effect of H 2 O 2 on caspase-3, the activation remained sufficient to induce a decrease in the alveolar number. The effect of ascorbylperoxide on alveolarization index was similar to the values previously reported in studies investigating the effect of parenteral nutrition [14,15]. …”
Section: Discussionsupporting
confidence: 86%
“…Alveolarization index represents the mean value for each animal of the number of intercepts between a standardized straight-line (1 mm) and histological structures calculated from four different fields of the same lung (200× magnification) [14,15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For mmu04810, Actin cytoskeleton plays a role in human pulmonary artery ECS [55]. For mmu00740, lung remodelling induced by exposure of total parenteral nutrition to ambient light is due to the interaction between vitamin C and peroxides generated by the exposure of riboflavin to light [56]. For mmu04060, the analysis of lung adenocarcinoma tissue specimens have demonstrated that the genes involved in these biological pathways have high rates of over-expression [57].…”
Section: Resultsmentioning
confidence: 99%
“…Peroxide concentrations range from 255 to 400 μM in LE TPN solutions, while they range from 100 to 175 μM3 6 10 16 in photoprotected preparations. The differences in intermediary metabolism might be associated with differences in peroxides or to other light-induced byproducts generated in the TPN solution 22 23…”
Section: Discussionmentioning
confidence: 99%